Recalcitrant Palmoplantar Pustulosis: Have You Considered Allergic Contact Dermatitis? - Neves, J (2021)
Palmoplantar pustulosis (PPP) is a chronic and relapsing disease of the palms and soles, which tends to be difficult to treat. Clas sically it was described as a subtype of psoriasis. Nowadays it is regarded as a separate entity, although plaque-type psoriasis affects concomi tantly many patients with PPP. A link between allergic contact dermatitis (ACD) and PPP has been described, and the former may encompass a potential to perpetuate the latter. Hereby we report two cases of difficult to treat plantar pustulosis. Underneath the dermatosis’s refractive nature was an allergic sensitization to potassium dichromate and cobalt chloride. Leather shoes and leather insoles were commonly worn, and both allergens are employed by the leather industry. Clinical remission was achieved in both cases with allergen eviction. Patch testing must be considered in cases of PPP without response to treatment. If relevant sensitization is found, allergen eviction measures are mandatory.